MEMBANGUN PROFESIONALISME GURU DALAM BINGKAI PENDIDIKAN KARAKTER - hanafi, Muhammad (Universitas Hasanuddin, 2017)
Teachers are professional educators with the primary task of educating, teaching, guiding, directing, training, assessing, and evaluating learners in early childhood education, primary education, and secondary education. Professional is a work or activity undertaken by a person and becomes a source of income of his life that requires expertise, skill or skill that meets certain quality or norm standards and requires professional education. As a profession, thecompetence that must be possessed by a teacher, namely personality competence, pedagogic competence, professional competence, and social competence. Teachers have a strategic role in the field of education, even other adequate educational resources are often meaningless if not accompanied by adequate teacher quality. Likewise, the opposite happen, if the quality teacher is poorly supported by other supporting resources are adequate, can also cause less optimal performance. In other words, teachers are at theforefront of improving the quality of education services and outcomes. In many cases, the quality of the education system as a whole is related to the quality of teachers. To that end, improving the quality of education should be done through efforts to improve the quality of teachers character. The professionalism of a teacher must be framed in character education, because to educate the character of the learner can only be done by a teacher of character. So,educating characters must be character, because the most effective way of educating is to set an example.Key words: Professionalism, character education, teachers, pedagogic systems, learners